Innovations in the payments system, systemic risks and challenges to central banking in Trinidad and Tobago - Seerattan, Dave ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Looks at the structure of the payments systems generally and in Trinidad and Tobago. Reviews the various payments instruments used in Trinidad and Tobago and attempts to delineate the implications for systemic risks and central bank policy flowing from these changes to the payments system.